Sophie Johnson, unicorn expert, is a detective genius - Hood, Morag (Illustrator) (Aladdin Books, 2020)
Sophie Johnson is on the case to find the Lion's missing tail, but she is so focused on rounding up suspects that she is missing her puppy (and new assistant) Bella's true detecting potential.